2005
DOI: 10.12693/aphyspola.107.240
|View full text |Cite
|
Sign up to set email alerts
|

Transients of Carrier Recombination and Diffusion in Highly Excited GaN Studied by Photoluminescence and Four-Wave Mixing Techniques

Abstract: Time-resolved photoluminescence and four-wave mixing techniques have been combined for studies of carrier relaxation dynamics in a highly photoexcited GaN epilayer. For a moderate excitation density below 1 mJ/cm 2 , carrier recombination was due to free carrier capture by deep traps. The characteristic time of carrier capture, τ e = 550 ps, was measured under deep trap saturation regime. The ambipolar diffusion coefficient for free carriers, D = 1.7 cm 2 /s, was estimated from the analysis of the transients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…3b). In the ELO layer, however, due to a larger dislocation density, we observed a gradual transfer from linear to bimolecular recombination only at higher excitation, with subsequent saturation of EC at reaching the threshold of stimulated recombination [2][3][4].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…3b). In the ELO layer, however, due to a larger dislocation density, we observed a gradual transfer from linear to bimolecular recombination only at higher excitation, with subsequent saturation of EC at reaching the threshold of stimulated recombination [2][3][4].…”
Section: Resultsmentioning
confidence: 73%
“…The previous works have demonstrated the applicability of time-resolved four-wave mixing (TR FWM) for investigation of carrier recombination and transport features in differently grown GaN heterostructures [1,2]: a novel possibility to determine the threshold of stimulated recombination [2,3], carrier localization dependent diffusion coefficient in InGaN alloys, decrease of the alloy structural quality at higher In content, evidenced by the decreasing carrier lifetime [3]. Complementary studies by using photoluminescence (PL) and time-resolved PL have confirmed a high sensitivity and advantages of FWM for studies of defect-density and excitation dependent carrier recombination peculiarities and transport in GaN heterostructures [2,[4][5][6]. However, the previous studies by TR FWM have been performed at 300 K.…”
Section: Introductionmentioning
confidence: 95%
“…2, two different regions are visible in the plots: at low excitation (< 0.4 mJ/cm 2 ), η increases with pump as η = I 0 2 and then a saturation of the diffraction efficiency takes place. It has been established that the mentioned regions are caused by two different physical processes: first, the band-to-band carrier generation increases the diffraction signal, but then the stimulated recombination evolves as the threshold carrier concentration is reached [18]. The saturation in the undoped REF1 is much stronger pronounced than in the doped samples MD1 and MD2, which we attribute to a lower efficiency of the stimulated recombination in the Fe-doped GaN.…”
Section: Light Induced Transient Grating (Litg) Techniquementioning
confidence: 77%
“…Dynamic holography provides optical configurations to create and monitor the spatial refractive index modulation n(x, t) = n 0 + ∆n(t) cos (Kx) as well relationship between the diffraction efficiency of a grating η = (π∆nd/λ) 2 , while the nonlinear optics gives quantitative ratios between the modulation mechanisms of optical properties and the modulation amplitude ∆n. In the given case, the refractive index change at 1064 nm (well below the band gap) is determined by free carrier density N according to Drude-Lorentz model: ∆n = −n eh ∆N , where the coefficient n eh is the refractive index change by one electron-hole pair n eh [3] and equals to ≈ 1 × 10 −21 cm −3 for GaN at the wavelength of the probe beam. This coefficient together with the thickness of excited region d determines the sensitivity of the FWM technique, i.e.…”
Section: Basic Principles Of Four-wave Mixing Techniquementioning
confidence: 99%
“…Direct relationship between nonresonant, light induced refractive index modulation ∆n(x, t) by nonequilibrium carriers ∆N (x, t) and holographic approach for monitoring dynamics of ∆n allowed development of innovative holographic measurement technique -the time-resolved (TR) four-wave mixing (FWM) on free carrier gratings. Recently TR FWM under picosecond excitation was applied for study of competition between nonradiative recombination at dislocations and radiative interband processes in GaN layers with varying dislocation density [1], determination of bimolecular recombination coefficient and its temperature dependence [2] in hydride vapor phase epitaxy grown (HVPE-grown) free standing films, control of stimulated emission threshold in lasing compounds [3], carrier localization effects in InGaN alloys by direct measurements of In-content dependent diffusion coefficient values and carrier lifetimes values [4], recombination activity of iron-related traps and dislocations in highly resistive GaN layers [5]. In epitaxial SiC, origin of fast decay transients of bipolar nonequilibrium carrier plasma was analysed [6].…”
Section: Introductionmentioning
confidence: 99%